The Evolution of China"s Sporting Diplomacy since 1949 : The History, Experience and Promotion Strategies = Razvoj sportske diplomacije u Kini od 1949. godine : povijesni razvoj, iskustva i promocijske strategije - An, Yalun (Array, 2021)
The sporting diplomacy in China, as an integral part of China"s overall diplomacy, unswervingly upholds the fundamental foreign policy goal of preserving world peace and promoting common development since New China was founded. After adopting the policy of reform and opening, the sporting diplomacy in China has made historical achievements through intensive participation in international sporting competitions, extensive involvement in international sporting organizations, active hosting of mega sports events, and frequent engagement in cultural sporting exchanges with other countries. In the last decade, with a constant increase in China"s economy, cultural soft power and international influence of sports, China makes an all-round effort in the pursuit of major countrywide sporting diplomacy with Chinese characteristics. Currently, despite the severe challenges outside China, Beijing is making smooth preparations for the 2022 Winter Olympic and Paralympic Games, which embraces another milestone in the diplomacy of sport in China. This paper analyzes decision environments, goals, actions and defining features of China"s sporting diplomacy in different periods and follows on to summarize practical experiences in the development of the sporting diplomacy in China. The paper shows that the resounding success of China"s sporting diplomacy can be attributed to its commitment to serving the country"s diplomatic strategy and core interests, its commitment to following the Chinese path of sporting diplomacy, and its commitment to the traditional Chinese value of peaceful development. Finally, emerging issues and promotion strategies are presented.